2019
DOI: 10.1097/md.0000000000014783
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of the esophagus complicated with poorly differentiated mucinous adenocarcinoma of the stomach

et al.

Abstract: Rationale:Primary malignant melanoma of the esophagus (PMME) is a rare malignancy that only accounts for <2% of all primary esophageal tumors. Here, we report the even rarer occurrence of PMME in combination with poorly differentiated mucinous adenocarcinoma of the stomach.Patient concerns:A 64-year-old man was presented to the hospital with >1 month of eating dysphagia. Enhanced computed tomography (CT) scan only found a space-occupying lesion in the lower esophagus with moderate enhancement. However, gastros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Therefore, these authors renewed the need to employ techniques such as massive gene sequencing to be able to search for biomarkers capable of predicting the response of PMME to anti-PD1 immunocheckpoint inhibitors. After another 38 cases of PMME [ 274 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 ], Endo F. et al [ 290 ] reported a case of a 70-year-old man who complained of dysphagia due to the presence of a polypoid lesion in the lower thoracic esophagus. Although the histopathological examination had provided the diagnosis of esophageal squamous carcinoma at first, with subsequent pT3N1M0 staging and clinical stage III, a histological re-evaluation after radical esophagectomy revealed the presence of atypical melanocyte cells positive for S-100 protein, Melan-A and HMB-45, and, therefore, PMME was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these authors renewed the need to employ techniques such as massive gene sequencing to be able to search for biomarkers capable of predicting the response of PMME to anti-PD1 immunocheckpoint inhibitors. After another 38 cases of PMME [ 274 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 ], Endo F. et al [ 290 ] reported a case of a 70-year-old man who complained of dysphagia due to the presence of a polypoid lesion in the lower thoracic esophagus. Although the histopathological examination had provided the diagnosis of esophageal squamous carcinoma at first, with subsequent pT3N1M0 staging and clinical stage III, a histological re-evaluation after radical esophagectomy revealed the presence of atypical melanocyte cells positive for S-100 protein, Melan-A and HMB-45, and, therefore, PMME was diagnosed.…”
Section: Discussionmentioning
confidence: 99%